THE EFFECT OF FISCAL POLICY ON ECONOMIC GROWTH IN INDONESIA - Aril Priyadipa; Khairil Anwar; Darmawati Darmawati; Sapna Biby; Darul Irfan (LPPM Universitas Malikussaleh, 2022)
This study was conducted in Indonesia within a period of 16 years from 2005-2020 using vector autoregression (VAR) analysis methods the purpose of this study to see the effect of fiscal policy (government revenue and expenditure) on economic growth, the results of the study obtained that using granger causality analysis that economic growth and government acceptance do not have a reciprocal relationship (causality) while government spending. It has a reciprocal relationship (causality) to economic growth while by using the VAR method economic growth does not have a negative and significant effect on itself, government acceptance has a positive and significant effect on economic growth and government spending negatively and significantly limited economic growth.